Analysis of floristic composition and structure as an aid to monitoring protected areas of dense rain forest in southeastern Brazil - Eliana Cardoso-Leite; Diego Sotto Podadera; Juliana Cristina Peres; Ana Carolina Devides Castello (Acta Botânica Brasílica, 2013)
To study forest composition and structure, as well as to facilitate management plans and monitoring programs, we conducted a phytosociological survey in the PE Caverna do Diabo State Park and the Quilombos do Médio Ribeira Environmentally Protected Area, both located within the state of São Paulo, Brazil. We analyzed 20 plots of 400 m² each, including only individuals with a circumference at breast height > 15 cm. We employed cluster analysis and ordination (principal component analysis and correspondence analysis), including species data and abiotic data. We evaluated 1051 individuals, belonging to 155 species in 48 families. Of those 155, 18 were threatened species, 33 were endemic species, and 92 (59.4%) were secondary species. The overall Shannon index was 4.524, one of the highest recorded for a dense rainforest in southeastern Brazil. We found that our sample plots fell into three blocks. The first was forest in which there had been human disturbance, showing low species richness, minimal density, and a small relative quantity of biomass. The second was undisturbed mature forest, showing a comparatively larger quantity of biomass. The third was mature forest in which there had been natural intermediate disturbance (dead trees), showing higher species richness and greater density. We identified various groups of species that could be used in monitoring these distinct forest conditions.